Pentingnya Penonton Aktif di Era Industri Televisi Indonesia Saat Ini - Rahmat Edi Irawan (Bina Nusantara University, 2013)
The study in this paper is motivated by the increasing reports or complaints against television delivered to the Indonesian Broadcasting Commission (KPI). This paper aims to look at how the shift from a passive audience or spectators into an active audience or spectators in giving feedback on television shows that they receive, which is now starting to look also at the television audience in Indonesia. The methodology in this paper is literature study, to see how the exercise of some mass communication theories, particularly regarding to the impact of television on the audience. Conclusions or the results of the study for this paper show that there is a shift from passive audience to active audience in the television industry in Indonesia today. In the past, many obstacles, such as repressive regime, no choices of programs and television stations as well as the lack of regulation and the regulator had made television audience in Indonesia become passive. While today, the empowering of the audience through various media and efforts made by KPI causes the condition changing, the audience begins to be active. It is indicated by the increase of his/her critical stances, with a number of complaints on the violation of regulations either through KPI or other mass media.